From Expert Clinician to Nurse Educator: Outcomes of a Faculty Academy Initiative. Issue 4 (July 2016) - Hinderer, Katherine A.; Jarosinski, Judith M.; Seldomridge, Lisa A.; Reid, Tina P.
Abstract : The Eastern Shore Faculty Academy and Mentorship Initiative, a collaborative program among 3 nursing programs in rural Maryland, was developed to facilitate the transition of expert clinicians from diverse backgrounds in clinical specialty areas with critical shortages to new roles as part-time clinical faculty. Initial outcomes include 32 Academy graduates, with 37.5% representing diverse backgrounds and 37.5% in needed clinical specialties. This initiative represents an innovative approach to meeting the challenges of the nursing faculty shortage through collaborative efforts and creative solutions.